Fabrication and testing of composites with oriented microstructures - Balane, Gadil Veronica Yvonne (Nanyang Technological University, 2024)
Electronic system design has been requiring critical attention and consideration especially since devices have been increasingly densely packaged. Effective heat dissipation and regulation is a crucial factor in system design to guarantee excellent device performance. Thermal Interface Materials (TIMs) are high thermal conducting materials used to fill the interfacial gap between two or more stacked electronic components and channel the heat to the heat sink. Composite made of hexagonal boron nitride (hBN) filler and polyvinylidene fluoride (PVDF) matrix presents as a prospective TIM. In this study, BN-PVDF composites are fabricated using the magnetically assisted slip casting (MASC) method. Optimum slurry concentration was determined by firstly deciding on the optimum PVDF concentration, which was identified to be 10wt% PVDF after visual inspection of pure PVDF films. Secondly, the BN concentration was varied to produce slurries of 20wt%, 30wt%, 40wt%, 45wt%, and 50wt% mBN. After subjecting the slurries to rheological characterization, and fabricating film and bulk samples for morphological characterization using SEM, 45wt% BN emerged to be the optimum slurry concentration. The 45wt% BN slurry was then used to create vertically, horizontally, and randomly aligned film and bulk samples to further realize the material’s thermal properties. The samples were subjected to heating and cooling processes, where it was established that the vertical alignment conducts heat the fastest. Lastly, the thermal conductivities of samples were measured. Despite the through-thickness thermal conductivity of the vertically aligned 45wt% mBN sample being the highest with a value of 0.821 Wm-1K-1, it remained incomparable to other BN polymer composites that were previously fabricated. Further optimization of the fabrication process could be carried out in future works specifically reduction of porosities by sintering or by filling the voids with silicone oil in order to improve its thermal conductivity value. Mechanical and electrical testing should also be conducted to provide a comprehensive material characterization and to determine the usefulness of BN-PVDF composite especially in high power density electronics.